Giant lipoma of the back affecting quality of life. Issue 3 (September 2015) - Guler, Olcay; Mutlu, Serhat; Mahirogulları, Mahir
Abstract Lipomas are benign tumours composed of adipose tissue. They may be localized in almost all body parts and may be in a giant form. Some of these giant lipomas may transform malignity and cause problems in daily living and detoriate quality of life. Mass localization also restrict body functions. In the present study, a 72-year-old man who presented with a mass enlarged in a time period of two years and because of this could not lie in the supine position, sit in an erect position and dress easily, go outside because of his physical appearance. With surgical treatment a 38 × 22 × 21 cm mass weighing 3575 g was successfully resected. Postoperative early phase complications did not occur. During 48 months of postoperative period, any recurrence was not detected and the patient was free of all his complaints. Cosmetic and functional results of the surgery and patient satisfaction were excellent. After surgery patient's quality of life was improved and restriction of body function was disappeared.